Improvement of Optical Extinction by Various Wideband Dielectrics with Ag and Aunanoparticle on Metal-dielectric-semiconductor Structure in Solar Cell - Sarkar, Partha; Panda, Saradindu; Maji, Bansibadan; Mukhopadhyay, Asish K. (Nanoscience & Nanotechnology-Asia, 2020)
Background: In this article, photonic extinction performance of Metal Dielectric Semiconductor (MDS) nanostructure has been improved by noble metallic nanosphere such as gold, silver and copper into various wideband dielectrics like silicon di-oxide, aluminum oxide and silicon nitride. Methods: Presently, Plasmonics gives very much interest and closely involves in the main domains of nanophotonics that can control of optical fields at the nanoscale level as well as it can concentrate and enhance the electromagnetic field on the nanometer scale especially in metal dielectric semiconductor (MDS) nanostructure. Results: In plasmonics, noble metals used as nanoparticle where density of electron gas which oscillates at surface Plasmon frequency so we investigate impact of various wideband dielectrics with nanoparticle size for enhancement of extinction in terms of absorption and scattering by using surface Plasmon resonance. Conclusion: At Plasmonic resonance the efficiency will be maximum. If the size of the metallic nanosphere increases, initially the efficiency increases up to a certain wavelength then it becomes sharply decreased.
Keywords: Plasmonics